Osnovni prostorski in demografski kazalci za območje alpske konvencije v Sloveniji - Ferreira, Andreja (Zbornik gozdarstva in lesarstva, 2005)
The Alpine Convention emerged from the recognition of the Alpine countries that it is necessary to protect the natural and cultural values and to support the sustainable development of the Alpine area. Slovenia is one of the signatories of this important international contract, which links together8 countries, 5.971 communities and more than 13 million inhabitants. In the present article, some of the basic indicators for the Slovenian area ofthe Alpine Convention are presented and compared with the entire country.
Keywords: Alpe; Alps; Alpska konvencija; environmental protection; nadmorska višina; prebivalstvo; raba tal; Slovenia; Slovenija; varstvo okolja